A model for non-uniform sediment transport induced by flushing in sewer channels. (15th October 2019) - Campisano, Alberto; Modica, Carlo; Creaco, Enrico; Shahsavari, Gashin
Abstract: A novel unsteady flow numerical model for the simulation of the transport of non-uniform non-cohesive sediment mixtures (SM) during flushing operation in sewers is presented in this paper. The model was applied to the case of a flush experimental test that was recently carried out in a combined sewer channel of the sewer system of Paris city that exhibits depositional problems due to relatively coarse sediments. The model output was compared to the results of the field experiments as well as to those obtained with a model for the transport of uniform sediments (US). The model for SM provided a reliable interpretation of the selective transport of the sediments deposited in the channel bed as induced by the flush. The comparison showed the model for SM to provide an enhanced description of the erosional effects of the flush on the deposits, including improved evaluation of the volume of sediments flushed out of the experimental channel in the field. Highlights: Novel modelling approach to evaluate removal of non-uniform sediment deposits by sewer flushing. Model compared with experimental results of a field flush test performed in a combined sewer channel in Paris. Suitable description of the selective transport of the deposited sediments obtained. Improved modelling of the flush erosional impact in comparison to models for uniform sediments. Opening perspectives of model development for the analysis of efficiency of sewer flushing techniques.